Effects of Ibuprofen topical gel on muscle soreness - Hyldahl, R. D.; Keadle, J.; Rouzier, P. A.; Pearl, D.; Clarkson, P. M. (Medicine & Science in Sports & Exercise, 2010)
Purpose: Muscle soreness is a common symptom after novel exercise and may influence exercise adherence. This study examined the effect of an ibuprofen topical gel and the effect of age and sex on muscle soreness after a gym exercise.